Pembelajaran Bahasa Indonesia di Perguruan Tinggi dalam Konteks Interkultural - Alfiati Alfiati (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
Indonesian Language Course is a lesson that develops students' ability to speak Indonesian properly and correctly, because mastery of Indonesian can be used as a measure of one's nationalism as an Indonesian nation. The Indonesian language course also aims to develop students' abilities in organizing ideas or concepts to be communicated to other parties so that there is continuous interaction between ideas and results in an effective knowledge transfer and management process. One of these integration efforts is through intercultural-based learning methods. With an intercultural-based learning process, students are expected to have intercultural competence (interkulturelle competent). Competence is what becomes the provision for adaptation and intercultural communication while maintaining an Indonesian identity and character.